Living in troubled times : A new political era - Montbrial, Thierry de (World Scientific, 2019)
This book analyzes the transformations in global politics and economics in the early 21st century, reflecting on instability, shifting power relations, and the search for new frameworks of governance. Thierry de Montbrial provides insights into the dynamics of international relations and the emergence of a new political era.